ETHICAL CORPORATE GOVERNANCE BASED ON ISLAMIC PERSPECTIVE - Dianidza Arodha (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
This study explores the concept of ethical corporate governance from an Islamic perspective, emphasizing integrating moral values and Shariah principles in modern organizational management. Unlike conventional corporate governance models that focus primarily on regulatory compliance and shareholder interests, the Islamic approach centers on accountability to Allah (God), ethical leadership (amanah), justice (adl), and social responsibility (maslahah). This paper analyzes key elements of corporate governance—such as transparency, accountability, fairness, and commitment—through the lens of Islamic teachings derived from the Qur'an and Hadith. By examining contemporary case studies and theoretical frameworks, the study demonstrates how Islamic ethical principles can strengthen governance structures, promote trust, and prevent corruption in both private and public institutions. The findings suggest that applying an Islamic ethical framework to corporate governance enhances organizational integrity and contributes to sustainable economic development and societal well-being. This research contributes to the growing discourse on ethical business practices and offers practical insights for Muslim-majority countries seeking to align corporate behavior with Islamic values.